Critical power in laboratory and field conditions using single-visit maximal effort trials - Triska, C.; Tschan, H.; Tazreiter, G.; Nimmerichter, A. (International Journal of Sports Medicine, 2015)
To compare critical power (CP) and the maximum work performed above CP (W') obtained from a single-visit laboratory test with a single-visit field test, 10 trained cyclists (VO2max 63.2±5.5 mL·min-1·kg-1) performed a laboratory and a field test. The laboratory test° consisted of 3 trials to exhaustion between 2-15 min and the field test comprised 3 maximal efforts of 2, 6 and 12 min, where power output was measured using a mobile power meter. CP and W' were estimated using 3 mathematical models (hyperbolic, linear work-time, linear power -1/time). The agreement between laboratory and field conditions was assessed with the 95% limits of agreement (LoA). CP was not significantly different between laboratory (280±33 W) and field conditions (281±28 W) (P=0.950). W' was significantly higher in laboratory (21.6±7.1 kJ) compared to field conditions (16.3±7.4 kJ) (P=0.013). The bias was -2.8±27 W (95% LoA: -55 to 50 W) and 6.4±5.1 kJ (95% LoA: -3.5 to 16.4 kJ) for CP and W', respectively. No differences between the mathematical models were found for CP and W' (P=0.054-1.000). Although CP was not significantly different between conditions, a high random variation does not support its interchangeable use. The mathematical model used has no influence on estimates of CP and W'.